Insulin receptor preserves mitochondrial function by binding VDAC1 in insulin insensitive mucosal epithelial cells. Issue 1 (26th November 2019) - Titone, Rossella; Robertson, Danielle M.
Abstract: Unlike many epithelial tissues, the corneal epithelium is insulin insensitive, meaning it does not require insulin for glucose uptake. In this study, we show that insulin differentially regulates mitochondrial respiration in two human mucosal epithelial cell types: insulin‐insensitive corneal epithelial cells and insulin‐sensitive bronchial epithelial cells. In both cell types, insulin blocks glycogen synthase kinase beta (GSK3β) activity. In the corneal epithelium however, insulin selectively regulates PTEN‐induced kinase 1 (PINK‐1)‐mediated mitophagy and mitochondrial accumulation of insulin receptor (INSR). While insulin blocked basal levels of PINK‐1‐mediated mitophagy in bronchial epithelial cells, mitochondrial trafficking of INSR was not detectable. We further show that in corneal epithelia, INSR interacts with the voltage‐dependent anion channel‐1 (VDAC1) in mitochondria and that INSR knockdown triggers robust mitochondrial fragmentation, alterations in mitochondrial polarization, and blocks the induction of PINK‐1‐mediated mitophagy. Collectively, these data demonstrate that INSR interacts with VDAC1 to mediate mitochondrial stability. We also demonstrate unique interactions between VDAC1 and other receptor tyrosine kinases, indicating a novel role for this family of receptors in mitochondria.